DINAMIKA KONTESTASI LEMBAGA ZAKAT DI KOTA MAKASSAR (STUDI DI BAZNAS DAN LAZNAS WAHDAH) - Usluddin Usluddin; Hasbi Hasbi (Fakultas Dakwah dan Komunikasi, 2020)
The presence of many zakat institutions in managing zakat, infaq and sadaqah nowadays is a fascinating thing. The zakat institution officially owned by the government of Makassar City which has succeeded in becoming a channel for distributing zakat especially ASN. However the presence of the other zakat institutions seemed to be an arena of contestation to win muzakki, which one of that was LAZNAS Wahdah Makassar, in which relying on the strength of their cadre networking. This research is qualitative field research with descriptive-analysis method. The conclusion of the research about the contestation dynamics of zakat institutions in Makassar City (Studied at BAZNAS and LAZNAS Makassar City, is namely (1) the dynamics of the miscoordination contestation especially BAZNAS vs LAZNAS and (2) the dynamics of reconciliation contestation especially LAZNAS vs. LAZNAS. In this study also revealed the factors that encourage muzakki in distributing zakat, namely: (1) Structural Factors and (2) Cadre Networking Factors. In addition, the efforts to avoid potential conflicts of contestation in zakat institution can be accomplished in 3 ways (1)zoning of the performance of zakat institution (2) develops the program Strategy Plan, and (3) Internal Improvement of zakat institutions